2005
DOI: 10.1051/0004-6361:20041707
|View full text |Cite
|
Sign up to set email alerts
|

Conservation laws and theorems of confinement and stability for a charged equatorial disk in a pulsar magnetosphere

Abstract: Abstract. For studying the nonaxisymmetric stability of the bounded electrosphere of an "aligned pulsar" (Michel's structure with polar domes and equatorial belt), Pétri et al. (2002) recently introduced a simplified but useful model in which all the charge-separated plasma located outside the magnetized rotating star is concentrated into a thin equatorial disk. In this paper, some aspects of this model are investigated analytically. It is shown that the equations governing the behaviour of the disk -in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…When there is no external source of charges feeding the magnetosphere, it has been found that the plasma remains confined in regions close to the equilibrium state as also shown by Aly (2005).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…When there is no external source of charges feeding the magnetosphere, it has been found that the plasma remains confined in regions close to the equilibrium state as also shown by Aly (2005).…”
Section: Introductionmentioning
confidence: 64%
“…The non linear development of this instability was studied by Pétri et al (2003), still in the framework of an infinitely thin disk model. When there is no external source of charges feeding the magnetosphere, it was found that the plasma remains confined in regions close to the equilibrium state, as also shown by Aly (2005). When however the disk can be fed by some charge source, Pétri et al (2003) have shown that the instability causes a cross-field transport of these charges in the equatorial disk, evolving into a net out-flowing flux of charges.…”
Section: Introductionmentioning
confidence: 86%
“…MHD type instabilities of non-neutral plasmas can lead to short time variability in the magnetosphere possibly related to radio emission fluctuations (Urpin 2014). Moreover, the evolution of the non-neutral plasma, especially in the disk, has to satisfy some conservation laws (Aly 2005) stipulating that an isolated disk, i.e. without particle injection, will remain confined in the vicinity of the neutron star.…”
Section: Stabilitymentioning
confidence: 99%
“…The differentially rotating disk is shown to suffer from diocotron instability [77,79,80], thus exhibits non-axisymmetric charge modulations and radial expansion [77], and the actual equatorial charge distribution likely is more complicated than just laminar flow around a simple torus, with macroparticles/vortices likely showing up [76] (also note that the disk is not bound by a trap surface, so there is no aforementioned self-maintenance mechanism at work to regulate the shape of the disk; nevertheless, the disk remains confined, at least in the absence of pair injection, and cannot escape to infinity [128]).…”
Section: Appendix A3 With Plasma: the Charge-separated Electrospheresmentioning
confidence: 99%